Pengaruh Current Ratio (CR), Debt to Equity Ratio (DER), Debt To Asset Ratio (DAR) dan Inventory Turnover (ITO) terhadap Laba Bersih pada Sub Sektor Pulp & Paper yang Terdaftar Di Bei Periode 2017-2021 - Lisa Utari (Universitas Batanghari Jambi, 2022)
This study will use the first 4 financial ratios, namely the current ratio, debt to equity ratio (DER), Debt to asset ratio (DAR) and Inventory Turnover (ITO). Where the Current ratio is the ratio used to measure a company's ability to meet short-term obligations, the Debt to equity ratio (DER) is the ratio used to analyze financial reports to show the amount of collateral available to creditors and Inventory Turnover (ITO) is the ratio used to see the extent to which the level of inventory turnover owned by a company. This research is to see how the effect of Current ratio, Debt o Equity Ratio, Debt to Assets Ratio, and Inventory Turn Over on net profit. The author draws the hypothesis that the Current ratio, Debt o Equity Ratio, Debt to Assets Ratio, and Inventory Turn Over have a significant effect on net income.The research methodology used is descriptive analysis method and statistical analysis method. The data used is secondary data. Hypothesis testing was carried out using the F test and t test, with a significance level of (α) 5%. Analysis data using statistical data processing software, namely SPSS version 25 for windows. The results of the study prove that the variables Current Ratio, Debt To Equity Ratio, Debt To Assets Ratio and Inventory Turn Over have a simultaneous effect on net income Y= -14,239 + 0428x1 - 10,665x2 + 24,056x3 - 2,285x4. Partially, the Inventory Turn Over variable has an effect on Net Income, while Current assets, Debt to equity ratio, and Debt to Assets ratio have no significant effect on net profit for the 2017-2021 period. The influence of the variables Current Ratio, Debt To Equity Ratio, Debt To Assets Ratio and Inventory Turn Over on net income is 37.8%. While the remaining 62.82% is explained by other variables outside the model.